Efektivitas Model Pembelajaran CPS Berbantuan LKPD Dalam MeningkatkanKemampuan Pemecahan Masalah di MTsN 3 Surabaya - Herdita Putri, Krishela; Maduri, Devi Indah; Mukarromah, Sa’ida Umi; Indayati, Tatik; Indiarti (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The purpose of this study was to determine the implementation and effectiveness of the Creative Problem Solving (CPS) learning model in improving students' problem-solving abilities in Ecology material for Grade VII. The research method used was an experiment with a quantitative research approach and also used a one-group pretest-posttest design. Data collection was carried out using observation sheets, pre-tests and post-tests. The validity test of the instrument used validity and reliability tests, normality tests, homogeneity tests, and T tests. The research findings showed that the CPS learning model was effective in improving students' problem-solving capacity in the ecology curriculum for grade VII. This was due to a significant difference between the pre-test and post-test scores, where the post-test scores were higher than the pre-test scores. Based on the research findings, it is recommended that the CPS learning paradigm be used in learning.